Random sampling of elementary flux modes in large-scale metabolic networks - Machado, Daniel; Soons, Zita (Bioinformatics, 2012)
Abstract. Motivation: The description of a metabolic network in terms of elementary (flux) modes (EMs) provides an important framework for metabolic pathway an
Gesehen am 13.07.2018